Meigs syndrome was misdiagnosed as a malignant ovarian tumor: a case report - Li, Hongmei; Xing, Yanli; Hong, Wei; Ma, Yangyang; Niu, Lizhi (Frontiers in Oncology, 2025)
BackgroundMeigs syndrome is characterized by the association of a benign ovarian tumor, typically an ovarian fibroma, with pleural effusion and ascites.Case summaryThis report presents a case of a 54-year-old woman who was misdiagnosed with malignant ovarian neoplasm due to the presence of significant abdominal distension and elevated CA125 levels. Initial imaging at multiple external facilities suggested a left-sided malignant ovarian tumor, leading to unnecessary delays in treatment. Upon admission to our institution in April 2024, imaging confirmed a large pelvic mass, and subsequent diagnostic procedures indicated a likely fibroma. Surgical intervention revealed a left ovarian thecoma, and post-operative pathology confirmed the diagnosis. Notably, CA125 levels decreased from 335.1 U/ml to 164.6U/ml following surgery, and the patient showed significant clinical improvement.ConclusionThis case underscores the importance of considering Meigs syndrome in patients presenting with ovarian masses, pleural effusions, and elevated CA125, to prevent misdiagnosis and ensure timely management.